STRATEGI PEREMPUAN DAYAK NGAJU DALAM PROGRAM REDD+ DI KALIMANTAN TENGAH - Nova Scorviana; Setiadi Setiadi (Jurnal Ilmiah Pendidikan Lingkungan dan Pembangunan, 2018)
The purpose of this research are to uncover and describing the role and strategy of Kalumpang women in DA-REDD+ program, that facilitated by KFCP. Ecofeminism approach used to finding Kalumpang women strategy, of looking at and treating nature. This approach is also intended to review the extent to which women's Kalumpang involvement in the DA-REDD+ KFCP. DA-REDD+ KFCP pilot project is one of the global framework related to climate change mitigation, saving the environment, by integrating the economics and sustainable prosperity through carbon stocks. The research was conducted in the Kalumpang village, Mantangai Kapuas District of Central Kalimantan Province, with an ethnographic approach. The data obtained by observation, participation observations, documentations, studies secondary data and in-depth interviews with informants who have been. The result showed that women are involved in a small part program, nursery and planting activities (reforestation), especially when filling the soil and planting seeds into polybags.While gender equality issues who was appointed by KFCP in the implementation of the program, has not been able to embrace all levels of society. Strategy undertaken by women Kalumpang also varies confront of the REDD+ program. There are so enthusiastic to follow each set of activities, some are then left and returned at the beginning of the activity.